Household food insecurity and children's oral health: Findings from the 2016–2018 National Survey of Children's Health. (30th November 2020) - Jackson, Dylan B.; Testa, Alexander
Abstract: Objectives: The purpose of the present study is to examine the association between household food insecurity and oral health problems among US children, and the role that socioeconomic, insurance, and oral health care utilization variables play in this association. Methods: A large, nationally representative sample of children from the 2016–2018 National Survey of Children's Health (NSCH) was employed in the present study ( N = 99, 962). Logistic regression and negative binomial regression were used to assess the influence of household food insecurity on diverse oral health problems and unmet oral health care needs. The Karlson–Holm–Breen (KHB) method was used to examine the attenuating roles of socioeconomic, insurance, and oral health care utilization variables. Results: Children in food‐insecure households exhibited significantly greater odds of all examined oral health problems as well as unmet oral health care needs. These associations were a) most pronounced in the case of moderate‐to‐severe food insecurity and b) partly explained by a subset of socioeconomic and insurance‐related variables. Conclusions: Household food insecurity is a potent risk factor for oral health problems and unmet oral health care needs among US children. Programmatic efforts to address household food insecurity may yield collateral benefits for the oral health of children. Furthermore, because socioeconomic status and insurance‐related variables explain part of the association, targeted interventions to improve these factors may improve oral health among at‐risk children.